2018
DOI: 10.20945/2359-3997000000052
|View full text |Cite
|
Sign up to set email alerts
|

The effect of levothyroxine treatment on left ventricular function in subclinical hypothyroidism

Abstract: Objective: Treatment of subclinical hypothyroidism (ScH), especially the mild form of ScH, is controversial because thyroid hormones influence cardiac function. We investigate left ventricular systolic and diastolic function in ScH and evaluate the effect of 5-month levothyroxine treatment. Subjects and methods: Fifty-four patients with newly diagnosed mild ScH (4.2 < TSH < 10.0 mU/L) and 30 euthyroid subjects matched by age were analysed. Laboratory analyses and an echocardiography study were done at the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…It was reported that compared with healthy people, the left ventricular systolic and diastolic function of SCH patients was slightly affected. Moreover, L-T4 treatment reversed the change of left ventricular systolic and diastolic function of SCH patients, but has no significant effect on systolic pressure [11]. A similar study also found that for children with hypothyroidism and ventricular diastolic dysfunction, L-T4 treatment can significantly improve left ventricular dysfunction [12].…”
Section: Introductionmentioning
confidence: 76%
“…It was reported that compared with healthy people, the left ventricular systolic and diastolic function of SCH patients was slightly affected. Moreover, L-T4 treatment reversed the change of left ventricular systolic and diastolic function of SCH patients, but has no significant effect on systolic pressure [11]. A similar study also found that for children with hypothyroidism and ventricular diastolic dysfunction, L-T4 treatment can significantly improve left ventricular dysfunction [12].…”
Section: Introductionmentioning
confidence: 76%
“…It was reported that compared with healthy people, the left ventricular systolic and diastolic function of SCH patients was slightly affected. Moreover, L-T4 treatment reversed the change of left ventricular systolic and diastolic function of SCH patients, but has no signi cant effect on systolic pressure [11]. A similar study also found that for children with hypothyroidism and ventricular diastolic dysfunction, L-T4 treatment can signi cantly improve left ventricular dysfunction [12].…”
Section: Introductionmentioning
confidence: 78%
“…Ozturk S. et al performed echocardiography in ScH patients and, using tissue Doppler imaging (TDI), measured the maximal systolic velocity of the mitral valve ring motion (S'), which is a parameter of LV systolic function. They showed a statistically significant reduction of S' in patients with ScH compared to the controlled group; however, levothyroxine treatment did not improve the S' [66].…”
Section: Subclinical Hypothyroidism (Sch) and The Cardiac Functions Mmentioning
confidence: 90%
“…Myocardial performance index (MPI), a parameter measuring global LV systolic function, is generally shown to be abnormal in ScH patients. MPI values can be reversed with levothyroxine treatment [66,67]. Global longitudinal strain (GLS) is a better parameter for measuring LV global systolic function, mainly when the ejection fraction (EF) is normal.…”
Section: Subclinical Hypothyroidism (Sch) and The Cardiac Functions Mmentioning
confidence: 99%